Investors Perspective of Various Disclosures in Corporate Annual Report - Vasudeva , Sakshi (Gyan Management Journal, 2016)
The companies in India are making disclosures related to their contribution towards non-financial areas rather than simply reporting financial figures. The present paper is an attempt to understand the pattern of decision making of investors and the importance of various componentsof annual report while making investment decisions. An effort is also made to understand the attitude of investor towards financial and non-financial disclosures and emerging concept known as integrated reporting. Exploratory analysis was done on the basis of 122 valid responses. The results showed that the respondents most likely make decisions by seeking advice from friends/family /colleagues and also on the basis of advice from specialists through print and audio /visual media. While making investment decisions, investors mostly read profit and loss figures,financial statistics/summary, dividend declared and executive summary. The most important non-financial information which was found to be highly relevant was ’Policies of the company towards its employees’;then ’Corporate Governance Report of the company’ and then ’Policies of the company towards impact on the environment’. The results also showed that there is scope of integrated reporting in India as investors want the information in the manner as perceived in the concept. The study recommends that companies should use results of the study and make more detailed disclosures covering the relevant aspects of both financial and nonfinancial information.